MANAGEMENT OF VILLAGE-OWNED ENTERPRISES (BUMDES) THROUGH THE FOOD COURT BUSINESS UNIT IN KATERUNGAN VILLAGE, KRIAN DISTRICT, SIDOARJO REGENCY - Dwiantoko, Meisya Putri; Rodiyah, Isnaini (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the management of the Village-Owned Enterprise (BUMDes) Barokah Makmur through its Pujasera unit in Katerungan Village, Krian District, Sidoarjo Regency, focusing on how the management functions of planning, organizing, actuating, and controlling are implemented to strengthen the local economy and empower the community. Method: A descriptive qualitative approach was employed using observations, interviews, and documentation, with data analyzed through Miles and Huberman’s interactive model, including data collection, reduction, display, and conclusion drawing. Results: The findings reveal that planning considered strategic location and culinary potential, although spatial layout optimization remains limited. The organizational structure is well-defined, yet only certain units, particularly Pujasera, consistently operate. The actuating process reflects high managerial commitment but is constrained by human resource limitations. Supervision is effectively conducted through formal and social mechanisms. Financially, Pujasera recovered from losses in 2021–2022, generating a net profit of IDR 26,905,044 in 2024 and contributing 40% to village revenue. Novelty: This study contributes to understanding adaptive management strategies in village enterprises by demonstrating how Pujasera’s transformation fosters sustainable local economic independence, emphasizing innovation through human resource development, organizational reinforcement, and systematic facility management.